The influence of art education on jewelry design - BAYBURTLU, ÇİMEN; ULUSMAN, LEYLA (E D P SCIENCES, 2016)
Principally, theory and practice should be in harmony. In Jewelry Design Programmes, the knowledge of light, colour and design should be thought on basis of theories and causations besides visuality and practice. The education of design provides the students an independent aspect and encourages researching and questioning when supported by theoretical knowledge as art history, aesthetics, sociology of art, arts policy and analyzation of works of arts. The fundamental thing in art education is an accurate definition of art and a correct specification of coordinates of art education in accordance with this definition. If universal art coordinates are not included in Jewelry Design Education's scope, it is possible to train craftsmen but not artists. It is a recognized truth that if a work of art has gained a universal value and protected it in time, then it is likely to talk about an artist and artistic values. Unique art works have their own creation laws and prove themselves in time.
Keywords: art; interdisciplinary art; jewelry; design